2022
DOI: 10.1007/s00259-022-05941-3
|View full text |Cite
|
Sign up to set email alerts
|

123I-MIBG imaging in heart failure: impact of comorbidities on cardiac sympathetic innervation

Abstract: Purpose Heart failure (HF) is a primary cause of morbidity and mortality worldwide, with significant impact on life quality and extensive healthcare costs. Assessment of myocardial sympathetic innervation function plays a central role in prognosis assessment in HF patients. The aim of this review is to summarize the most recent evidence regarding the clinical applications of iodine-123 metaiodobenzylguanidine (123I-MIBG) imaging in patients with HF and related comorbidities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…In this scenario, repeated evidence has shown that alterations in 123 I-MIBG imaging parameters represent independent prognostic factors, even when advanced age, comorbidities and chronic conditions (chronic kidney disease, diabetes and obesity) negatively concur to disease progression and outcome. 33 The ADMIRE-HF study included 964 patients with HF in NYHA class II-III to determine the independent predictive value of 123 I-MIBG imaging on all-cause mortality and on a composite endpoint of death/death-equivalent events. The authors demonstrated, through multiple multivariate risk modelling, the impact of cardiac sympathetic innervation on patient outcomes compared with other clinical measurements including brain natriuretic peptide (BNP) levels and LVEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, repeated evidence has shown that alterations in 123 I-MIBG imaging parameters represent independent prognostic factors, even when advanced age, comorbidities and chronic conditions (chronic kidney disease, diabetes and obesity) negatively concur to disease progression and outcome. 33 The ADMIRE-HF study included 964 patients with HF in NYHA class II-III to determine the independent predictive value of 123 I-MIBG imaging on all-cause mortality and on a composite endpoint of death/death-equivalent events. The authors demonstrated, through multiple multivariate risk modelling, the impact of cardiac sympathetic innervation on patient outcomes compared with other clinical measurements including brain natriuretic peptide (BNP) levels and LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is worth mentioning that the assessment of the risk/benefit ratio is often particularly challenging in the clinical practice, even in areas in which the different factors contributing to outcomes intrinsically overlap, making it difficult to discriminate the relative contribution of each component. In this scenario, repeated evidence has shown that alterations in 123 I‐MIBG imaging parameters represent independent prognostic factors, even when advanced age, comorbidities and chronic conditions (chronic kidney disease, diabetes and obesity) negatively concur to disease progression and outcome 33 . The ADMIRE‐HF study included 964 patients with HF in NYHA class II–III to determine the independent predictive value of 123 I‐MIBG imaging on all‐cause mortality and on a composite endpoint of death/death‐equivalent events.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-123 metaiodobenzylguanidine (123I-MIBG) scintigraphy is a safe and helpful imaging technique to evaluate cardiac innervation [ 29 ]. Although this technique has been widely studied in HFrEF, current knowledge regarding cardiac sympathetic innervation in HFpEF is limited.…”
Section: Multimodality Imaging and Natriuretic Peptidementioning
confidence: 99%
“…We previously discussed another phenethylguanidine radiotracer, [ 18 F]mFBG, for neuro‐oncology applications (see section 3.2 ). Both [ 123 I]MIBG and [ 18 F]mFBG is a NET‐targeted radiotracer, which can also be used in cardiology for imaging myocardial presynaptic nerve density [70] [48] .…”
Section: Radiotracer Applications Of Scidymentioning
confidence: 99%
“…Both [ 123 I]MIBG and [ 18 F]mFBG is a NETtargeted radiotracer, which can also be used in cardiology for imaging myocardial presynaptic nerve density. [70] Our recent collaboration with the Rotstein lab described the optimized and automated radiosynthesis of [ 18 F]mFBG in RCYs of 24 � 1% with A m of 30-95 GBq/μmol. [48] Preclinical cardiac PET studies in healthy rats revealed favourable uptake (~3 SUV) and monoexponential washout kinetics.…”
Section: Miscellaneousmentioning
confidence: 99%